Rescue of degenerating neurons and cells by stem cell released molecules: using a physiological renormalization strategy. Issue 9 (2nd May 2019) - Maguire, Greg; Paler, Lee; Green, Linda; Mella, Rosa; Valcarcel, Maria; Villace, Patricia
Abstract: Evidence suggests that adult stem cell types and progenitor cells act collectively in a given tissue to maintain and heal organs, such as muscle, through a release of a multitude of molecules packaged into exosomes from the different cell types. Using this principle for the development of bioinspired therapeutics that induces homeostatic renormalization, here we show that the collection of molecules released from four cell types, including mesenchymal stem cells, fibroblast, neural stem cells, and astrocytes, rescues degenerating neurons and cells. Specifically, oxidative stress induced in a human recombinant TDP‐43‐ or FUS‐tGFP U2OS cell line by exposure to sodium arsenite was shown to be significantly reduced by our collection of molecules using in vitro imaging of FUS and TDP‐43 stress granules. Furthermore, we also show that the collective secretome rescues cortical neurons from glutamate toxicity as evidenced by increased neurite outgrowth, reduced LDH release, and reduced caspase 3/7 activity. These data are the first in a series supporting the development of stem cell‐based exosome systems therapeutics that uses a physiological renormalization strategy to treat neurodegenerative diseases. Abstract : We show that the molecules released from stem cells can rescue neurons and other cells from oxidative stress and from glutamatergic toxicity. Our approach for therapeutic development is to renormalize the physiology by reintroducing the molecules to the diseased tissue that were present in the normal tissue.